Entre a arquitectura e a natureza. O abrigo de madeira na Serra do Soajo - Sara Canossa Ventura Gomes (2016)
In areas as unique as the Parque Nacional da Peneda-Gerês (PNPG), one of forty six protectedareas in Portugal, the binomial architecture/nature is brought into confrontation in a verypeculiar way. It is a territory full of history, culture and traditions, also characterized byclimatic and geographical conditions that combine to form the built and natural landscapethat is present today.The project presented in this work is located in the Camping and Caravanning site ofTravanca that is located in the PGNP in the Serra do Soajo. This tourist resort was builtat an old cattle branda and preserves some of the shelter structures used in the practice ofpastoralism, a traditional activity in this territory.Besides being close to Porta do Mezio - one of five Portas that welcomes visitors to the PNPG- the recente change in management and the need to revitalize the camping site where keyfactors to justify a new plan for the site. It is proposed to build one or more shelters, usinga concept that, since early times, is closely linked to human relationship with nature. Theproject focus on the use of wood as building material for shelters, taking advantage of itscapabilities to integrate into the environment, its flexibility, lightness and self-assembly.